Affinity monolith chromatography: A review of general principles and recent developments. Issue 24 (12th August 2021) - Poddar, Saumen; Sharmeen, Sadia; Hage, David S.
Abstract: Affinity monolith chromatography (AMC) is a liquid chromatographic technique that utilizes a monolithic support with a biological ligand or related binding agent to isolate, enrich, or detect a target analyte in a complex matrix. The target‐specific interaction exhibited by the binding agents makes AMC attractive for the separation or detection of a wide range of compounds. This article will review the basic principles of AMC and recent developments in this field. The supports used in AMC will be discussed, including organic, inorganic, hybrid, carbohydrate, and cryogel monoliths. Schemes for attaching binding agents to these monoliths will be examined as well, such as covalent immobilization, biospecific adsorption, entrapment, molecular imprinting, and coordination methods. An overview will then be given of binding agents that have recently been used in AMC, along with their applications. These applications will include bioaffinity chromatography, immunoaffinity chromatography, immobilized metal‐ion affinity chromatography, and dye‐ligand or biomimetic affinity chromatography. The use of AMC in chiral separations and biointeraction studies will also be discussed.